Elk Distributions Relative to Spring Normalized Difference Vegetation Index Values. (27th June 2010) - Smallidge, Samuel T.; Baker, Terrell T.; VanLeeuwen, Dawn; Gould, William R.; Thompson, Bruce C.
Abstract : Rocky Mountain elk ( Cervus elaphus ) that winter near San Antonio Mountain in northern New Mexico provide important recreational and economic benefits while creating management challenges related to temporospatial variation in their spring movements. Our objective was to examine spring distributions of elk in relation to vegetative emergence as it progresses across the landscape as measured by remote sensing. Spring distributions of elk were closely associated with greater photosynthetic activity of spring vegetation in 2 of 3 years as determined using NDVI values derived from AVHRR datasets. Observed elk locations were up to 271% greater than expected in the category representing the most photosynthetic activity. This association was not observed when analyses at a finer geographic scale were conducted. Managers facing challenges involving human-wildlife interactions and land-use issues should consider environmental conditions that may influence variation in elk association with greener portions of the landscape.